D

[Algebra] Easiest way to solve this?

9 viewed last edited 1 year ago
Hanna Owens
1
I have this formula 3x^(2) - 3 = 0 I know there are two answers for this, x = -1 and x = 1 I think I am missing some rule, or I am doing it wrong. What would be the most efficient or easiest way? I divided by 3 -> x^(2) -1 = 0 Then moved the 1 to the right, or +1 both sides -> x^(2) = 1 And then I took the square root on both sides so x = √1
Vivekanand Vellanki
1
Why do you think you got it wrong? \sqrt{1}=\pm 1 To see this, find (-1)^2 -1 \times -1 = 1 Hence, (-1)^2=1 and -1=\sqrt{1}